(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The scarcity of natural resources involves the recurrence of multiple individual contingencies (IC) with more immediate and greater individual consequences, producing a less immediate cumulative effect (CE), harmful to the group. The nature of the resources, school items to be donated or tokens exchangeable for money, was manipulated on the frequency of responses of ethical self-control. Four triads chose numbered rows in a chart controlled by the experimenter computer. The even choices produced three tokens for the individual, and the odd ones one. The choices affected a common reserve by deducting their tokens, readjusted by cycle. In the Baseline there was only IC; in Condition A the responses produced a CE for tokens; in Condition B, the CE was items; and in C, both. The results indicate that the nature of the CE does not change the responses to resource use, and the effect of other variables.